Capacitive Properties of the Binder‐Free Electrode Prepared from Carbon Derived from Cotton and Reduced Graphene Oxide. Issue 12 (3rd September 2017) - Ma, Wenhui; Chang, Yunzhen; Han, Gaoyi; Xiao, Yaoming; Fu, Dongying; Chang, Yahui
Abstract : The binder‐free composite films of reduced graphene oxide (rGO) and activated carbon derived from cotton (aCFC) have been fabricated and used as electrodes for electrochemical capacitors (ECs) to avoid the decrease of capacitive performance in traditional process caused by the additional binder. The optimal aCFC is prepared at 850 °C when the mass ratio of carbon and potassium hydroxide is 1 to 4. The optimal composite film prepared from the mass ratio of aCFC/GO=2/1 exhibits porous structure, and has a specific surface area of 849.6 m 2 g −1 and a total pore volume of 0.61 mLg −1 . Based on the two‐electrode system testing in 6.0 mol/L KOH electrolyte, the optimal composite has specific capacitance of about 202 Fg −1, 374 mFcm −2 and 116 Fcm −3 in terms of mass, area and volume, and shows excellent rate capability and good cyclic stability (91.7% retention of the initial capacitance after 5000 cycles). Furthermore, the assembled solid‐state ECs by using KOH/polyvinyl alcohol as electrolyte show good mechanical stability and capacitive performances after repeated bending cycles. It is proved that this method is effective to fabricate binder‐free electrodes for ECs and will open up a novel route for the reuse of waste cotton. Abstract : The binder‐free composite films of reduced grapheme oxide (rGO) and activated carbon derived from cotton (aCFC) have been fabricated. The optimal composite films aCFCG‐2 exhibits porous structure and has a larger specific surface area, a total pore volume, large specific capacitance, and good cyclic stability. The assembled solid‐state ECs show good mechanical stability and capacitive performances after repeated bending cycles.